In vitro evaluation of the immunomodulatory and antibacterial activities of calcitriol (1,25-dihydroxy-vitamin D3) as a potential application for aerobic vaginitis treatment - preliminary study results - Anna Tomusiak-Plebanek; Grażyna Więcek; Edyta Golińska; Magdalena Strus (BMC Microbiology)
Abstract Background Aerobic vaginitis (AV) is a state of abnormal vaginal microbiota, which is associated with increased numbers of aerobic, enteric bacteria and inflammation of the vaginal epithelium. Anti-microbial treatment combined with anti-inflammatory therapy could be useful in the treatment of this condition. It is known that calcitriol, the active form of vitamin D, plays an important role in modulating the immune response in several inflammatory diseases. The aim of this preliminary study was to evaluate in vitro the influence of calcitriol on the immune response of human vaginal epithelial cells to bacterial infection. Moreover, we assessed the anti-bacterial properties of calcitriol, as well as its synergistic activity with antibiotics that are used for the treatment of AV. Results Human vaginal A431 epithelial cells were treated with calcitriol (100 nM) and then stimulated with thermally inactivated strains of AV-associated bacteria (Escherichia coli, Enterococcus faecalis, Streptococcus agalactiae), or first stimulated with heat-treated bacteria and then incubated with calcitriol (30 nM). After 24 h, 48 h, and 72 h post-infection, culture supernatants were collected, and levels of pro-inflammatory cytokines IL-6 and IL-1β were analyzed using enzyme-linked immunosorbent assays (ELISA). As it turned out, calcitriol treatment pre- or post-bacterial stimulation of vaginal epithelial cells significantly decreased the levels of IL-6 and IL-1β compared to cells stimulated only with bacteria. Downregulation of pro-inflammatory cytokines was more frequently significant when cells were pre-treated with calcitriol. Additionally, this study evaluated the anti-bacterial properties and synergistic activity of calcitriol with antibiotics by determining the Minimal Inhibitory Concentration (MIC) using colorimetric, Resazurin-based microdilution method detecting the active metabolism of bacteria. As a result, calcitriol by itself did not exhibit clinically relevant anti-bacterial activity; however, when combined with antibiotics, calcitriol significantly reduced the MIC values. Conclusions The results of this preliminary study confirm that calcitriol treatment influences cytokine-mediated immune response during infection and indicate that it can be effective in enhancing antibiotic activity. Such properties could be very useful in the treatment of inflammatory diseases. However, conclusions regarding the potential use of calcitriol in the treatment of AV require further confirmation in in vivo studies as well as in well-designed clinical trials.